Egg oiling as an effective management technique for limiting reproduction in an invasive passerine - Facundo Fernandez-Duque; Robyn L. Bailey; David N. Bonter (Avian Conservation and Ecology, 2019)
The House Sparrow (Passer domesticus), native to Europe and Asia, has been introduced globally and is now one of the most ubiquitous birds in the world. In North America, these invasive passerines compete with native species for nest cavities, which are often limited. Because of the difficulties of extirpating an invasive species and the growing desire from the public to help in conservation matters, we sought to test a potential technique for managing invasive cavity-nesting passerines that could be successfully deployed by professionals and citizen scientists alike. Previous studies demonstrate that applying vegetable oil to eggs is a nontoxic management technique often used to manage unwanted waterfowl. Further, egg oiling is a technique that is acceptable to a large segment of the public. This study assesses the efficacy of applying vegetable oil for preventing House Sparrow eggs from hatching, reducing the number of fledged young, prolonging incubation time, and delaying renesting attempts by the adults. We sprayed treatment clutches once with approximately 0.8 ml of vegetable oil early in the developmental period and subsequently monitored nests every 3-4 days. The application of vegetable oil to treated eggs was 100% effective at preventing hatching and, thus, preventing any offspring from fledging. Furthermore, the adults in the treatment group incubated their eggs for nearly twice as long as the adults at control nests, reducing their opportunity to produce more clutches later in the season. Given the availability, low cost, and effectiveness of applying vegetable oil to eggs to prevent the reproductive output of invasive cavity-nesting passerines, we propose that this method can be easily implemented by wildlife managers as well as trained nest box stewards.